Experimental electronic structures of the Fe IV =O bond in S=1 heme vs. nonheme sites: Effect of the porphyrin ligand - Augustin Braun; Leland B. Gee; Max D. J. Waters; Anex Jose; Michael L. Baker; Michael W. Mara; Jeffrey T. Babicz; Melanie A. Ehudin; David A. Quist; Ang Zhou; Thomas Kroll; Charles J. Titus; et al. (Proceedings of the National Academy of Sciences, 2025)
High-valent Fe IV =O species are common intermediates in biological and artificial catalysts. Heme and nonheme S=1 Fe IV =O sites have been synthesized and studied for decades but little quantitative experimental comparison of their electronic structures has been available, due to the lack of direct methods focused on the iron. This study allows a rigorous determination of the electronic structure of a nonheme Fe IV =O center and its comparison to an Fe IV =O heme site using 1s2p resonant inelastic X-ray scattering (RIXS) and Fe L-edge X-ray absorption spectroscopy (XAS). Further, variable temperature magnetic circular dichroism (VT-MCD) of the ligand field transitions, combined with nuclear resonance vibrational spectroscopy of the two S=1 Fe IV =O systems show that the equatorial ligand field decreases from a nonheme to a heme Fe IV =O site. Alternatively, RIXS and Fe L-edge XAS combined with MCD show that the Fe d π orbitals are unperturbed in the Fe IV =O heme relative to the nonheme site because the strong axial Fe-O bond uncouples the Fe d π orbitals from the porphyrin π -system. As a consequence, the thermodynamics and kinetics of the H-atom abstraction reactions are actually very similar for heme compound II and nonheme Fe IV =O active sites.